{Electrochromic behavior of NiO thin films deposited by e-beam evaporation at room temperature} - Pereira, Sónia; Gonçalves, Alexandra; Correia, Nuno; Pinto, Joana; Pereira, Lu\'ıs; Martins, Rodrigo; Fortunato, Elvira (Solar Energy Materials and Solar Cells, 2014)
n/a
n/a
Keywords: Chromogenic materials; electrochromic devices; Nickel oxide; Thermal evaporation